The Use of Chokes to Improve the Quality of the Static Frequency Converter - Kalinin L.P.; Zaitsev D.A.; Golub I.V.; Tirshu M.S. (Problems of the Regional Energetics)
The aim of the work is to develop technical measures to improve the quality of the power transmission process through electrical link, which contains a frequency converter based on a PST (phase-shifting transformer) with circular rotation of the output voltage phase in relation to the input, made according to the triangle scheme and controlled by means of power electronics. To achieve this goal, the use of longitudinal inductive elements (chokes) has been proposed as one of the measures that significantly improves the controlled mode parameters in the process of frequency conversion. The problem has been solved by performing computational experiments on simulation models of electrical links, combining two power systems with a frequency of 60 and 50 Hz, respectively. The structure of electrical links at various stages of the study has included several circuit variants of a frequency converter (single-channel circuit, dual-channel with reversing control winding sections, dual-channel circuit without reversing control winding sections) and has developed by authors earlier. In the process of research, the value of inductance of chokes has been changed, as well as their place of connection. The controlled transmission's characteristics have been analyzed as well. The novelty of the work lies in the use of longitudinally included inductive elements as a possible solution to the problem of improving the quality of power transmission when combining power systems with different operating frequencies using static frequency converters. The optimal values of the parameters of inductive elements, comprised between 0.03-0.035Hn for all circuit versions of the converter, have been identified.